Effect of football or strength training on functional ability and physical performance in untrained old men. (5th June 2014) - Andersen, T. R.; Schmidt, J. F.; Nielsen, J. J.; Randers, M. B.; Sundstrup, E.; Jakobsen, M. D.; Andersen, L. L.; Suetta, C.; Aagaard, P.; Bangsbo, J.; Krustrup, P.
Abstract : The effects of 16 weeks of football or strength training on performance and functional ability were investigated in 26 (68.2 ± 3.2 years) untrained men randomized into a football (FG; n = 9), a strength training (ST; n = 9), or a control group (CO; n = 8). FG and ST trained 1.6 ± 0.1 and 1.5 ± 0.1 times per week, respectively, with higher ( P < 0.05) average heart rate (HR) (∼ 140 vs 100 bpm) and time >90%HRmax (17 vs 0%) in FG than ST, and lower ( P < 0.05) peak blood lactate in FG than ST (7.2 ± 0.9 vs 10.5 ± 0.6 mmol/L). After the intervention period (IP), VO2 max (15%; P < 0.001), cycle time to exhaustion (7%; P < 0.05), and Yo‐Yo Intermittent Endurance Level 1 performance (43%; P < 0.01) were improved in FG, but unchanged in ST and CO. HR during walking was 12% and 10% lower ( P < 0.05) in FG and ST, respectively, after IP. After IP, HR and blood lactate during jogging were 7% ( P < 0.05) and 30% lower ( P < 0.001) in FG, but unchanged in ST and CO. Sit‐to‐stand performance was improved ( P < 0.01) by 29% in FG and 26% in ST, but not in CO. In conclusion, football and strength training for old men improves functional ability and physiological response to submaximal exercise, while football additionally elevates maximal aerobic fitness and exhaustive exercise performance.